The influence of personal and work-related factors on teachers' commitment during educational change: A study on UAE public schools - Ibrahim, Ali; Aljneibi, Fawzia (Heliyon, 2022)
Despite the significant role that committed teachers play in the lives of their students and for implementing educational reforms and changes, the topic of teachers' commitment has not received due attention in the United Arab Emirates (UAE). Therefore, this study attempted to investigate teachers' commitment at one large school district in the UAE where the system has been undergoing substantial change for the last two decades. Specifically, this paper explored personal and school-related variables that could have impacted teachers' commitment. In this study, teachers' commitment is explored through two main dimensions: organizational commitment, which included affective, normative, and continuance commitment, and commitment to teaching, which included commitment to the profession, students, and the subject. The study utilized a quantitative research methodology where commitment was assessed through a survey completed by 737 teachers from 40 schools in Al Ain School District. The results revealed that teachers' commitment to teaching scored higher than their organizational commitment. The study also found that commitment increased with age, length of service, and staying at the same school, and it dampened when teachers had heavy teaching loads, taught multiple subjects, and were given exhausting non-teaching duties. The study concluded with specific recommendations that could help school principals and educational policymakers increase teachers' commitment. Organizational commitment; Commitment to teaching; Educational change; United Arab Emirates.